The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2010
DOI: 10.1177/0886260510372937
|View full text |Cite
|
Sign up to set email alerts
|

The Psychosocial Consequences of Child Sexual Abuse in Ethiopia: A Case-Control Comparative Analysis

Abstract: Child sexual abuse (CSA) continues to be a pressing public health concern around the globe. Few existing reports, however, indicate the alarming rate at which the problem is increasing in sub-Saharan Africa. The present study is designed to investigate the psychosocial consequences of sexual abuse among child survivors in Ethiopia who were abused mainly through early marriage, rape, and child prostitution. Data are collected from 318 such CSA survivors-and 318 matched, non-sexually abused, normal controls- usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…Over (75%) of the participants had average scores of self-esteem while (6.3%) had low self-esteem scores at baseline. The findings are consistent with Wondie et al’s (2011) study among sexually abused child survivors in Ethiopia, which found that sexually abused children had a lower degree of self-worth. Similarly, the findings of the current study are consistent with a study done in India among rural adolescent girls who had average and low self-esteem (Nagar et al 2008).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Over (75%) of the participants had average scores of self-esteem while (6.3%) had low self-esteem scores at baseline. The findings are consistent with Wondie et al’s (2011) study among sexually abused child survivors in Ethiopia, which found that sexually abused children had a lower degree of self-worth. Similarly, the findings of the current study are consistent with a study done in India among rural adolescent girls who had average and low self-esteem (Nagar et al 2008).…”
Section: Discussionsupporting
confidence: 91%
“…A study was conducted by Wondie et al (2011) among 318 sexual abuse survivors in Ethiopia, using the Rosenberg self-esteem scale and the findings indicated that the abused children had a lower degree of self-worth compared to non-abused children. Also Burack et al (2006) found that maltreated children had lower self-worth and depression than their peers, which led to self-harm, risk taking behaviors and poor performance in school.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…These include a greatly increased risk of revictimization (Ibanga, 2011; Jewkes, Levin, Mbananga, & Bradshaw, 2002), increased risk of HIV infection and poor physical health (Jewkes, Dunkle, Nduna, Jama, & Puren, 2010; Reza et al, 2009), higher child death rates (Mathews, Abrahams, Jewkes, Martin, & Lombard, 2012), and exposure to transactional sex (Cluver, Orkin, Boyes, Gardner, & Meinck, 2011; Peltzer & Pengpid, 2008). In addition, there are similar outcomes of abuse as those found in the West, such as delinquency, substance abuse (Brown et al, 2009; Jewkes et al, 2006; Morojele & Brook, 2006), depression, and suicide (Cluver, Gardner, & Operario, 2009; Fincham, Altes, Stein, & Seedat, 2009; Frank-Briggs & Alikor, 2010; Oladeji, Mkanjoula, & Gureje, 2010; Wondie, Zemene, Tafesse, Reschke, & Schröder, 2011). However, these may have even more severe consequences for children in Africa due to low levels of access to mental health and social services (WHO, 2011b).…”
Section: Introductionmentioning
confidence: 82%
“…The prevalence of child sexual abuse was high (68.7%), among which verbal harassment filled most part (51.4%), followed by sexual intercourse (18%), and unwelcome kissing (17.1%). [ 10 ] Most of the victims are under 15 years of age and experienced psychological problems after being abused such as suicide, low degree of positive self-worth and sexual dysfunction [ 10 14 ]. Hospitals only focused on the physical healing while these psychological problems are often ignored [ 11 ].…”
Section: Resultsmentioning
confidence: 99%